Tari Melayu Sarumpun di Sanggar Sarai Sarumpun Kota Padang: Tinjauan Koreografi - Salsabilla Faiqaersya; Desfiarni Desfiarni (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
The purpose of this study is to examine the performance of Sarumpon Malay dance at the Sarumpon Serai Sanggar in Padang city. The type of qualitative research is the descriptive method of analysis. The research tool is an independent researcher, assisted by supporting devices such as cameras, notebooks, and mobile phones. Data were collected through literature studies, observations, interviews and literature. The function of data analysis includes interpretation, interpretation, and conclusion drawing. The results of the study show that the Sarumpun Malay Dance Choreography carried out by choreographer Randi Rivandika is a new dance creation that is worked on with a choreographic approach. The choreography of the Sarumpun Malay Dance can be seen from the choreography process and the form of choreography. The choreography process includes exploration, improvisation, and composition. The atmosphere that appears in the Sarumpun Malay Dance is joyful. The choreography of this dance is as follows: (1) The movements of female dancers consist of Awal Masuk motion, Putar kanan motion, Pose motion, Ayun Berputar motion, Bukak Selendang motion, Melenggang Selendang motion, Putar Step motion, Malenggang Berpandang motion, Berpandang motion, Step Berbalas motion, Petik Kanan Kiri motion, Ayun Salendang motion, Lenggang Pola S motion, Pose Duduk motion, Maambiak Salendang motion, Lenggang Putar Berbalas motion, Lenggang Bergoyang motion, Selendang Bergoyang motion, Putar Bahu motion, Pose Terakhir motion. The movements of the male dancer consist of Awal motion, Menyambut motion, Tangan Maayun motion, Manusuak Silang motion, Malenggang Step motion, Lenggang Berpandang motion, Langkah Silang motion, Lenggang Pola S motion, Step Berpasangan motion, Lenggang Sauk motion, Lenggang Patiak motion, Step Lingkaran motion, Putar Bahu motion, Pose Akhir motion,(2) Vertical, horizontal and diagonal Floor Patterns. (3) using the composition of large groups. (4) The musical instruments used are tambua, accordion, talempong, bansi, and bass. (5) The property used is a scarf. (6) The costume used is a Malay costume creation and the makeup used for the female dancer is beautiful makeup.